ASSESSING THE IMPACT OF INCREASING SMALL BUSINESS COMPETITIVENESS ON ECONOMIC DEVELOPMENT - Melibаevа Gulxоn (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study examines the role of enhancing small business (SME) competitiveness in fostering economic growth and national integration in Uzbekistan. It highlights the challenges of low competitiveness identified by researchers and international institutions, emphasizing the need for a national strategy. The research discusses various dimensions of competitiveness, from products to national economies, stressing that improving SME competitiveness is critical for regional and national economic stability. Existing assessment methods, such as matrix analyses, are explored, noting their limitations and the necessity for adaptable frameworks that account for diverse factors influencing competitiveness. The study underscores the importance of SMEs in driving innovation, job creation, and market diversification, advocating for a more dynamic and comprehensive approach to competitiveness.